2001
DOI: 10.1096/fj.00-0833hyp
|View full text |Cite
|
Sign up to set email alerts
|

Hypothesis: inappropriate colonization of the premature intestine can cause neonatal necrotizing enterocolitis

Abstract: Neonatal necrotizing enterocolitis (NEC) is a major cause of morbidity in preterm infants. We hypothesize that the intestinal injury in this disease is a consequence of synergy among three of the major risk factors for NEC: prematurity, enteral feeding, and bacterial colonization. Together these factors result in an exaggerated inflammatory response, leading to ischemic bowel necrosis. Human milk may decrease the incidence of NEC by decreasing pathogenic bacterial colonization, promoting growth of nonpathogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
254
1
7

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 383 publications
(268 citation statements)
references
References 60 publications
6
254
1
7
Order By: Relevance
“…This is evident from the lack of NEC in preterm gnotobiotic pigs fed formula (42). The patterns of bacterial colonization are particularly important for preterm neonates because of their increased sensitivity to bacterial colonization (9,29), with aberrant bacterial growth causing severe gut dysfunction and disease (15,37). Delivery mode and diet are determinants of initial colonization and development of the bacterial assemblages in the infant gut (17,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is evident from the lack of NEC in preterm gnotobiotic pigs fed formula (42). The patterns of bacterial colonization are particularly important for preterm neonates because of their increased sensitivity to bacterial colonization (9,29), with aberrant bacterial growth causing severe gut dysfunction and disease (15,37). Delivery mode and diet are determinants of initial colonization and development of the bacterial assemblages in the infant gut (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Despite precautions and the initial administration of total parenteral nutrition (TPN), NEC remains the most common gut disease afflicting preterm neonates (9).…”
mentioning
confidence: 99%
“…20 Furthermore, the preterm infant is exposed to bacteria in the neonatal intensive care unit, where the frequent use of broad-spectrum antibiotics affects the colonisation of health-promoting bacteria. 21 The choice of feed plays an important role in the establishment of intestinal flora. Bifidobacterium is a predominant organism found in the intestinal tract of breastfed infants.…”
Section: The Bifidogenic (Prebiotic) Effect Of Human Milk Oligosacchamentioning
confidence: 99%
“…By contrast, similar amounts of bacteroides and bifidobacterium are found in formula-fed infants, as well as components of the more pathogenic species, such as Staphylococcus, Escherichia coli and Clostridia. 21 An extraordinary characteristic of the intestinal environment of breastfed infants is the selective nourishment and protective support provided by the intestinal microbiotia. 22 The term "prebiotic" was introduced and defined by Gibson and Roberfroid as "a non-digestible food ingredient that beneficially affects the host by selectively stimulating the growth and/or activity of one or a limited number of bacteria in the colon".…”
Section: The Bifidogenic (Prebiotic) Effect Of Human Milk Oligosacchamentioning
confidence: 99%
“…S. boulardii, for which there is a risk of hematogenous dissemination in immunocompromised patients, was effective in inhibiting the recurrence of episodes of Clostridium difficile infection [70]. Although not all studies have confirmed the effectiveness of probiotics treatment in the prevention of AAD, a 2009 review has shown that effectiveness is mainly related to the strain used [71]; the studies have also confirmed that there is sufficient clinical evidence to support the use of Lactobacillus rhamnosus GG and S. boulardii strains in the treatment of antibiotic-associated diarrhea [72].…”
Section: Antibiotic-associated Diarrheamentioning
confidence: 99%